Об асимптотике потенциала счетной эргодической цепи Маркова - Москальцова, Н.В.; Шуренков, В.М. (Український математичний журнал, 1993)
Для певного класу функцій f доведено збіжність за Абелем потенціалу ∑n≥o Pⁿf(i) однорідного ергодичного ланцюга Маркова в зліченному фазовому просторі. Зроблено ряд висновків, корисних для погреб ЦГТ для ланцюгів Маркова, зокрема, умова, еквівалентна скінченносіі другого моменту для часу першого повернення до стану. For a class of functions f, the convergence in Abel's sense is proved for the potential ∑n≥o Pⁿf(i) of a uniform ergodic Markov chain in a countable phase space. Several corollaries are obtained which are useful from the point of view of the possible application to CLT (the central limit theorem) for Markov chains. In particular, we establish the condition equivalent to the boundedness of the second moment for the time of the first return into the state.